2013
DOI: 10.1117/1.jbo.19.1.011018
|View full text |Cite
|
Sign up to set email alerts
|

Single-virus tracking approach to reveal the interaction of Dengue virus with autophagy during the early stage of infection

Abstract: Dengue virus (DENV) is one of the major infectious pathogens worldwide. DENV infection is a highly dynamic process. Currently, no antiviral drug is available for treating DENV-induced diseases since little is known regarding how the virus interacts with host cells during infection. Advanced molecular imaging technologies are powerful tools to understand the dynamics of intracellular interactions and molecular trafficking. This study exploited a single-virus particle tracking technology to address whether DENV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 45 publications
3
27
0
Order By: Relevance
“…Here, we report findings that suggest a biphasic response of autophagy to DENV infection, where DENV infection initially activates and then later on inhibits autophagy. Although it has been reported by several groups that multiple components of the autophagy pathway are required for DENV replication (4,6,7,(27)(28)(29), we demonstrate here that DENV activates autophagy only during the early infection stage. Moreover, we established that, by 24 h after infection with the NGC strain, autophagosome formation is inhibited and lysosomal degradation of AVs is reduced.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Here, we report findings that suggest a biphasic response of autophagy to DENV infection, where DENV infection initially activates and then later on inhibits autophagy. Although it has been reported by several groups that multiple components of the autophagy pathway are required for DENV replication (4,6,7,(27)(28)(29), we demonstrate here that DENV activates autophagy only during the early infection stage. Moreover, we established that, by 24 h after infection with the NGC strain, autophagosome formation is inhibited and lysosomal degradation of AVs is reduced.…”
Section: Discussionmentioning
confidence: 70%
“…Autophagic flux is determined by the capacity of the cell to degrade forming autophagosomes, which occurs within minutes (25), and AV content increases upon disruption to lysosomal activity. It is commonly reported that DENV infection increases AV number as detected by high-resolution microscopy (6,7,24,26,27) and Western blot analysis of lipidated LC3-II levels (5,6,28,29). Notably, in autophagosomes colocalizing with lysosomes, pronounced pH-dependent quenching of green fluorescent protein (GFP)-LC3 fluorescence (30) was not observed (7), suggesting that DENV may reduce lysosomal acidification and so disrupt lysosomal function.…”
mentioning
confidence: 99%
“…Tracking experiments were performed as previously described (34) with minor modifications. In brief, 2 ϫ 10 5 HeLa cells were seeded in a 35-mm glass-bottom culture dish (MatTek, USA) and incubated overnight at 37°C.…”
mentioning
confidence: 99%
“…This interaction is required for the inhibition of autophagosome maturation and fusion with the lysosomes. [68][69][70]73 While iLIR could detect several WxxL motifs in TRS1 sequence, a single one in an intrinsically disordered region was identified for ICP34.5 whose sequence (64-RQWLHV-69) is quite well conserved among 4 strains of HSV-1 and one strain of HSV-2. However, to date, there is no evidence of association between ICP34.5 and LC3 proteins.…”
Section: Viruses Inhibiting Autophagymentioning
confidence: 99%
“…Studies have shown that NS1 protein from Dengue virus type 2 (DENV-2) colocalizes with LC3 and that DENV-2 particles and autophagosomes travel together during viral infection. 58,74 In contrast to DENV-2, NS1 protein from DENV-3 displays a low level of colocalization with LC3. 75 Sequence alignment of NS1 proteins from DENV-2 and DENV-3 showed that they are highly conserved.…”
Section: Viruses Activating Autophagymentioning
confidence: 99%